Effects of motivational climate, type of school and gender on students’moral competences in their daily life and physical education - Parisi, Joanna; Mouratidou, Katerina; Koidou, Eirini; Tsorbatzoudis, Haralambos; Karamavrou, Sofia (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The investigation of moral issues in physical education (PE) has received considerable attention over the last two decades. Moral competence is regarded as one of the fundamental learning goals in contemporary PE curriculum. Aim of Study. The goals of the present study were: a) to determine effects of motivational climate on students’ moral competence in conjunction with the school type and student’s gender, in everyday life and PE; and b) to examine possible relations among the developmental stages of moral competence in daily life and during PE. Material and Methods. The study sample comprised 428 high school students aged 12 to 15 years. Three questionnaires were administered: a) Moral Judgment Test, b) Moral Judgment Test in Physical Education, c) Students’ Perceptions of School/Classroom Goal Questionnaire. Results. The ANOVA revealed: a) a significant interaction effect of gender and motivational climate together on students’ moral competence both in their daily life and during physical education; and b) a significant interaction effect of gender and school type together on students’ moral competence in their daily life. No significant effects of motivational climate, gender and school type separately were found. The analysis indicated positive correlations among all six moral stages in daily life and the corresponding moral stages in physical education settings. Conclusions. The results show that the factors of gender and motivational climate, and gender in combination with school type are more significant to moral competence than if considered separately. Another notable finding of this study is a strong relationship between moral stages in daily life and those during physical education. Further research that will consider key factors of moral development and school intervention programs targeting moral competences is needed
Keywords: moral competence; motivational climate; school; art school